2016
DOI: 10.1186/s13063-016-1456-4
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the efficacy of dexamethasone in the treatment of patients with persistent acute respiratory distress syndrome: study protocol for a randomized controlled trial

Abstract: BackgroundAlthough much has evolved in our understanding of the pathogenesis and factors affecting outcome of patients with acute respiratory distress syndrome (ARDS), still there is no specific pharmacologic treatment for ARDS. Several clinical trials have evaluated the utility of corticoids but none of them has demonstrated a definitive benefit due to small sample sizes, selection bias, patient heterogeneity, and time of initiation of treatment or duration of therapy. We postulated that adjunctive treatment … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
36
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(37 citation statements)
references
References 41 publications
(37 reference statements)
0
36
0
1
Order By: Relevance
“…As a potent anti-inflammatory and anti-fibrotic drug, low doses of methylprednisolone (DEPO-Medrol or SOLU-Medrol) have the potential to prevent an extended cytokine response and may accelerate resolution of pulmonary and systemic inflammation in pneumonia [83,84]. Recently, many medical researchers believe that corticosteroids, especially methylprednisolone, may improve dysregulated immune response caused by sepsis (possible complication of infection with COVID-19) and increase blood pressure when it is low [85].…”
Section: Corticosteroidsmentioning
confidence: 99%
“…As a potent anti-inflammatory and anti-fibrotic drug, low doses of methylprednisolone (DEPO-Medrol or SOLU-Medrol) have the potential to prevent an extended cytokine response and may accelerate resolution of pulmonary and systemic inflammation in pneumonia [83,84]. Recently, many medical researchers believe that corticosteroids, especially methylprednisolone, may improve dysregulated immune response caused by sepsis (possible complication of infection with COVID-19) and increase blood pressure when it is low [85].…”
Section: Corticosteroidsmentioning
confidence: 99%
“…The DEXA-ARDS trial a multicenter, randomized controlled study in patients with moderate to severe ARDS persistent beyond 24 h was recently concluded and results due to be published [83] . Patients were randomized to dexamethasone 20 mg per day for 5 d followed by 10 mg per day for 5 d or placebo with ventilator-free days as primary outcome.…”
Section: Ardsmentioning
confidence: 99%
“…Currently, there are several studies in progress to examine the efficacy of steroids for the treatment of the COVID-19 and the results should be carefully interpreted in the clinical context. Accordingly, the administration of steroids may be considered in patients with severe COVID-19 who have worsening asthma or chronic obstructive pulmonary disease, severe septic shock requiring vasopressors, and ARDS [116][117][118]. If steroids are used, the occurrence of hyperglycemia, hypernatremia, and hypokalemia should be monitored closely and corrected [116,119].…”
Section: • Steroidsmentioning
confidence: 99%
“…Accordingly, the administration of steroids may be considered in patients with severe COVID-19 who have worsening asthma or chronic obstructive pulmonary disease, severe septic shock requiring vasopressors, and ARDS [ 116 117 118 ]. If steroids are used, the occurrence of hyperglycemia, hypernatremia, and hypokalemia should be monitored closely and corrected [ 116 119 ].…”
Section: Evaluation By External Expertsmentioning
confidence: 99%